Organizational Model of Regional Socio-Economic Territorial Management - Anopchenko, Tatiana Y.; Pryadko, Irina A.; Paytaeva, Kometa T.; Dubskaya, Oksana S.; Murzin, Anton D. (International Journal of Economics and Financial Issues, 2015)
The problem of accounting risk management of socio-economic development of territories has several aspects. Along with the relative novelty of the scientific development management, risk management tasks in industrial urbanization have not yet received sufficient methodological support. This article defined directions and tasks of captive insurance mechanism at the regional level, disclosed the peculiarities of captive insurance companies proposed mechanisms for its effective functioning. As a result, the study proposed a model of regional organization of risk management, the essence of which is to combine units monitoring organization and functional environment, to analyze the factors and assess the level of risk, as well as reference and methodological information. It is recommended to account for the industry-specific risk organizational structure of management and identify characteristics of the information flows three-component scheme of risks. Keywords: Model, Regional Management; Socio-Economic Risk; Risk Management; Insurance Mechanisms JEL Classifications: G22; L14; R11